Transition from pediatric to adult care. Are we prepared for this reality? - Urrea-Sepulveda, Ángela Mabel; Tovar-Añez, María Belén (Universidad y Salud, 2020)
Introduction: Survival of pediatric patients with chronic diseases is increasing worldwide, a trend that is also seen in Colombia. Most of these patients will make the transition to adulthood and adult medical services. Objective: To analyze the transition process of patients with chronic diseases from pediatric to adult care and describe the characteristics, barriers, risks, and consequences of this process. Materials and methods: A literature review search for related information. Results: 50 articles were selected from different academic journals. The assembled information was used to describe: (i) definitions of chronic disease, (ii) transition and transfer to adult care, (iii) risks of adolescents with chronic diseases, (iv) preparation and the different steps to make the transition, and (v) special considerations. Conclusions: The existing literature highlights the importance of undertaking an essential transition process to ensure the maintenance of health in patients with chronic diseases. However, in Colombia there are no guidelines or literature on the subject.